The Outsized Role of Salps in Carbon Export in the Subarctic Northeast Pacific Ocean. Issue 1 (31st December 2022) - Steinberg, Deborah K.; Stamieszkin, Karen; Maas, Amy E.; Durkin, Colleen A.; Passow, Uta; Estapa, Margaret L.; Omand, Melissa M.; McDonnell, Andrew M. P.; Karp‐Boss, Lee; Galbraith, Moira; Siegel, David A.
Abstract: Periodic blooms of salps (pelagic tunicates) can result in high export of organic matter, leading to an "outsized" role in the ocean's biological carbon pump (BCP). However, due to their episodic and patchy nature, salp blooms often go undetected and are rarely included in measurements or models of the BCP. We quantified salp‐mediated export processes in the northeast subarctic Pacific Ocean in summer of 2018 during a bloom of Salpa aspera . Salps migrated from 300 to 750 m during the day into the upper 100 m at night. Salp fecal pellet production comprised up to 82% of the particulate organic carbon (POC) produced as fecal pellets by the entire epipelagic zooplankton community. Rapid sinking velocities of salp pellets (400–1, 200 m d −1 ) and low microbial respiration rates on pellets (<1% of pellet C respired day −1 ) led to high salp pellet POC export from the euphotic zone‐up to 48% of total sinking POC across the 100 m depth horizon. Salp active transport of carbon by diel vertical migration and carbon export from sinking salp carcasses was usually <10% of the total sinking POC flux. Salp‐mediated export markedly increased BCP efficiency, increasing by 1.5‐fold the proportion of net primary production exported as POC across the base of the euphotic zone and by 2.6‐fold the proportion of this POC flux persisting 100 m below the euphotic zone. Salps have unique and important effects on ocean biogeochemistry and, especially in low flux settings, can dramatically increase BCP efficiency and thus carbon sequestration. Key Points: High salp abundances combined with unique features of salp ecology and physiology lead to their outsized role in the biological pump During a summer salp bloom in the northeast Pacific Ocean, salp‐mediated carbon export increased the amount and efficiency of carbon export Salps, especially in otherwise low flux settings, can increase carbon sequestration in the ocean